Implementasi Kebijakan Perda No 19 Tahun 2001 Dalam Pengaturan dan Pembinaan Pedagang Kaki Lima di Kawasan Jalan Cendana dan Lambung Mangkurat Kota Samarinda - Moch Rudhin Hadi Wahyudi; Muhammad Jamal Amin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The implementation of Regional Regulation No. 19 of 2001 aims to regulate and guide street vendors. Through this regulation, it is hoped that street vendors (PKL) will be better organized and contribute to regional revenue. The implementation of this policy is evaluated using indicators such as communication, commitment, organizational structure, and resources. This research aims to determine the extent to which the implementation of this regulation is effective in regulating and guiding street vendors. The data collection technique employs the 3P approach (People, Place, and Paper).The research findings indicate that the regulation has not been well implemented, as evidenced by the continued presence of street vendors trading on streets and sidewalks. Communication, including socialization efforts, has not been effective. The resource that needs improvement is human resources, while financial resources should be used more efficiently. Obstacles to the implementation of this regulation include the lack of awareness among street vendors about the regulation, their continued operation in prohibited areas, and insufficient facilities and infrastructure. Supporting factors include the dynamic development of regional law, effective communication, and support from various parties.